Associations between home injury falls and prior hospitalizations in community dwelling older adults: A population case-crossover study. Issue 2 (February 2020) - Adams, Christy M.; Tancredi, Daniel J.; Bell, Janice F.; Catz, Sheryl L.; Romano, Patrick S.
Highlights: First population study describing temporal patterns between acute care hospitalization and post-discharge home falls in older adults. A case-crossover design reduces confounding from the multifactorial and individual nature of older adult fall risk. Acute care hospitalizations are associated with post-discharge injury falls in older adults, with highest risk 0–90 days after discharge. Temporal patterns of deteriorating health prior to hospitalization and index fall suggest complex causality of post-discharge falls. Abstract: Objective: The purpose of this study was to examine risk factor and temporal associations between acute care hospitalization and post-discharge home injury falls in a population-based analysis sample of community dwelling older adults. Methods: We applied a unidirectional case-crossover design to a retrospective analysis sample derived from healthcare administrative data from all non-federal licensed hospitals in the State of California. The analysis sample was comprised of California residents age 65 years or older with a record of treatment for injury fall occurring at home from January 1, 2014 to December 31, 2014. A conditional Poisson regression with fixed person effects and a robust estimator of variance was used to calculate the incidence rate ratio of acute care admissions during the 90 day period immediately preceding an injury fall, with the period of 360–271 days prior to index fall as reference. Results: The rate of acute care admissions was 121% greater (IRR: 2.21; 95% CI 2.15–2.27) during the 90 days immediately preceding the index injury fall than 181–360 days prior. Period effects on rates of admissions were significantly higher in the acute care treatment subsample (IRR 2.63; 95% CI 2.51–2.76) than the emergency department treatment subsample (IRR 2.00; 95% CI 1.94–2.07). Discharge to post-acute care facilities; discharge to home health and Elixhauser comorbidity index all significantly modified period effects on acute care admissions. Conclusions: Older adults have an increased risk of falling at home after being discharged from an acute care hospitalization, with highest risk occurring during the 90-day post-discharge period. Special consideration should be given to assessing hospital-associated changes in fall risk among geriatric patients prior to discharge directly home. Discharge planning should include efforts to reduce home fall risk during the period of transition from hospital care.